Keterbatasan sdm negara berkembang dan persaingan secara langsung perusahaan digital negara maju dalam ekonomi digital pada presidensi g20 pada 2022 - Pande Putu Sariasih; Ni Luh Kardini; Ni Putu Yuli Tresna Dewi (STIMI Handayani Denpasar, 2023)
This study aims to determine the limitations of developing country human resources and direct competition for digital companies from developed countries in the digital economy in the G20 presidency in 2022. The population and sample in this study were all 50 employees of CV WS Teknologi. Data analysis was carried out using the research instrument test, classical assumption test and multiple linear regression analysis. The variable of limited human resources has a negative effect on the digital economy with a t-count value of -2.591 and a significance of 0.013. The digital company competition variable has a positive and significant effect on the digital economy with a t-count value of 6.631 and a significance of 0.000. The variable of limited human resources has a negative effect on the G20 presidency with a t-count value of -3.930 and a significance of 0.000. the digital company competition variable has a positive and significant effect on the G20 presidency with a t-count value of 2.674 and a significance of 0.049. It can be concluded that the variables of limited human resources, digital company competition and the digital economy have a positive and significant effect on the G20 presidency with an F-count value of 32.782 and a significance of 0.000.